2022
DOI: 10.1039/d1fd00067e
|View full text |Cite
|
Sign up to set email alerts
|

A GPx-mimetic copper vanadate nanozyme mediates the release of nitric oxide fromS-nitrosothiols

Abstract: Although reactive oxygen and nitrogen species (ROS/RNS) such as hydrogen peroxide (H2O2), nitric oxide (NO), hydroxyl radical (OH.), superoxide (O2-) etc. play crucial roles in redox biology and cellular signaling,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Typical examples are the GPx-like catalytic reactions of CuV 2 O 6 with GSH and H 2 O 2 , which differ greatly from the previously reported V 2 O 5 nanowires. 51 As shown in Fig. 2A and B, the absence of peaks at 1150 cm −1 and 930-940 cm −1 in Raman and infrared spectra indicated that no V-peroxide species formed.…”
Section: Qiaochu Zhangmentioning
confidence: 77%
See 2 more Smart Citations
“…Typical examples are the GPx-like catalytic reactions of CuV 2 O 6 with GSH and H 2 O 2 , which differ greatly from the previously reported V 2 O 5 nanowires. 51 As shown in Fig. 2A and B, the absence of peaks at 1150 cm −1 and 930-940 cm −1 in Raman and infrared spectra indicated that no V-peroxide species formed.…”
Section: Qiaochu Zhangmentioning
confidence: 77%
“…A detailed study based on experiments and theoretical calculations found that the {010} and {100} facets were more active than {001} because of their unsaturated surfaces, with {010} being the most active. Following these pioneering studies, other V-based nanomaterials, such as V 2 C MXenzyme, 47,80 orthovanadate NP, 81,82 MIL-47(V) MOF, 48 VN 4 single-atom, 83 MnV 2 O 6 , 51 ZnV 2 O 6 , 51 and CuV 2 O 6 , 51 also exhibited excellent GPx-like activities. As shown in Fig.…”
Section: Vanadium-basedmentioning
confidence: 98%
See 1 more Smart Citation
“…[51] In addition, researchers have also synthesized many nanozymes with GPx-like activities, which can convert endogenous prodrugs (e.g., S-nitrosoglutathione, GSNO) to NO. [52][53][54][55] Weng et al made a polydopamine coating containing HKUST-1 MOF on stainless steel to mimic the function of ECs. They found that the HKUST-1 MOF coating could catalyze GSNO decomposition to generate NO, similar to natural enzymes.…”
Section: No Generationmentioning
confidence: 99%
“…[ 51 ] In addition, researchers have also synthesized many nanozymes with GPx‐like activities, which can convert endogenous prodrugs (e.g., S‐nitrosoglutathione, GSNO) to NO. [ 52–55 ] Weng et al. made a polydopamine coating containing HKUST‐1 MOF on stainless steel to mimic the function of ECs.…”
Section: No Generationmentioning
confidence: 99%